Involvement in agro-tourism activities among communities in Desa Wawasan Nelayan villages on the east coast of Malaysia - Fahmi, Zaim; Hamzah, Azimi; Muhammad, Mahazan; Md. Yassin, Sulaiman; Abu Samah, Bahaman; Alby, Jeffrey Lawrence D'Silva; Mohamed Shaffril, Hayrol Azril (Canadian Center of Science and Education, 2013)
Over the years, most developing countries across the globe have identified agro-tourism activities as being able to assist their respective country’s development. Malaysia is no exception to this; the country has emphasized agro-tourism as a significant tool of development and poverty eradication, and perhaps, at the same time, a key strategy by which to address the problem of rural migration. The Fisheries Development Authority of Malaysia, also known as LKIM, has been playing a part in responding to the government’s call to develop the agro-tourism industry in Malaysia. LKIM has taken steps towards formulating an agro-tourism program for fishing communities called Desa Wawasan Nelayan. The purpose of this paper is to determine the level of involvement in agro-tourism amongst fishing communities in the east coast region of Malaysia. The study was conducted amongst 220 respondents from two villages in Terengganu and Kelantan. The findings of the research reveal that despite the government’s intervention in promoting agro-tourism activities throughout the nation, the level of involvement amongst respondents is still at a moderate level.